Unlearning Troubled Business Models: From Realization to Marginalization. Issue 3 (June 2016) - Rezazade Mehrizi, Mohammad H.; Lashkarbolouki, Mojtaba
Abstract : To cope with technological, economic and institutional changes, organizations need to innovate their business models (BM) by both developing new BMs and reducing their reliance on troubled BMs. While the development of new BM has been discussed in the literature, little systematic studied have examined how firms deal with the challenges arising from their troubled existing business models (unlearning BM). Based on two longitudinal case studies, we propose a process model that that constitute four stages of BM unlearning: "realizing", "revitalizing", "parallelizing", and "marginalizing". We discuss how unlearning dynamics help us to understand the importance of both single- and double-loop unlearning, to consider the double-faceted nature of BM (holistic and component-based), and to recognize the complex temporal dynamics of BM unlearning. Accordingly, we articulate four traps: "cognitive trap" (during realizing), "confidence trap" (during revitalizing), "mixing trap" (during parallelizing), and "reversion trap" (during marginalizing). We comment on the practices companies might adopt in dealing with these challenges.